SISTEM MONITORING KUALITAS UDARA DALAM RUANGAN MELALUI DETEKSI GAS, SUHU, DAN KELEMBABAN BERBASIS IOT - M. Ramadhan Syahrul Al Qodr; Hudzaifah Nabil Amrullah; Faris Fadhil Dhiaulhaq; Susilawati Sobur (PT. Saha Kreasi Indonesia, 2025)
This study aims to design and implement an indoor air quality monitoring system based on the Internet of Things (IoT) using the MQ-135 and DHT11 sensors. The MQ-135 sensor is employed to detect hazardous gases such as carbon monoxide (CO), carbon dioxide (CO₂), and volatile organic compounds (VOCs), while the DHT11 sensor measures temperature and humidity. Data from both sensors are processed by an ESP32 microcontroller and displayed locally through an OLED screen, as well as transmitted to the Blynk platform for remote monitoring. Testing was conducted in a room measuring approximately 8×6 meters under three conditions: normal air, cigarette smoke exposure, and post-smoking. The results show that gas concentration levels increased from 150–200 ppm (normal) to 800–900 ppm during smoking, then decreased to 450–550 ppm five minutes after the smoke dissipated. The system successfully monitored air quality changes in real-time with high sensitivity. These findings indicate that integrating IoT-based sensors provides an efficient and low-cost solution for indoor air quality monitoring.